Implementing deep learning approaches in storytelling methods for early childhood education - Ningsih, Suria; Aryani, Nini; Rahayu, Swandra (Thufuli, 2026)
The integration of deep learning approaches into storytelling methods represents a promising pedagogical innovation in early childhood education (ECE). This qualitative descriptive study examined how kindergarten teachers implement deep learning principles—specifically meaningful, mindful, and joyful learning—through storytelling activities. Data were collected through classroom observations, in-depth teacher interviews, and documentary analysis at a kindergarten in Indonesia. Findings indicate that lesson planning already reflects constructive alignment between learning objectives, material selection, and interactive activities. In implementation, meaningful learning and joyful learning aspects were well developed, as evidenced by children's capacity to retell stories and connect narratives to personal experience, and their high level of enthusiasm throughout the sessions. However, mindful learning—particularly reflective questioning and higher-order thinking—remained at an emerging stage and requires further reinforcement. The study concludes that storytelling, when scaffolded with deep learning principles, fosters holistic child development encompassing cognitive, linguistic, and socio-emotional domains. These findings contribute practical insights for ECE curriculum development and teacher professional training in implementing deep and meaningful learning approaches.